2006
DOI: 10.1007/s00436-006-0159-2
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate components of Taenia crassiceps metacestodes display Th2-adjuvant and anti-inflammatory properties when co-injected with bystander antigen

Abstract: Common helminth infections promote Th2-skewed immune responses in their hosts. We have studied the role of intact carbohydrate structures on Taenia crassiceps compounds in the induction of biased type 2 and anti-inflammatory immune responses on peptidestimulated T cells by using DO11.10 transgenic (OVA Tg) mice. While OVA Tg mice co-injected with OVA peptide [323][324][325][326][327][328][329][330][331][332][333][334][335][336][337][338][339]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 50 publications
2
31
0
Order By: Relevance
“…For example, macrophages were implicated in the resolution of dextran-sodium sulfate-induced colitis in mice infected with Schistosoma mansoni (41). Given the possibility that helminthderived molecules might induce anti-inflammatory type macrophages (7,11), we tested the effect of an extract of H. diminuta and ES products on macrophage function. Analysis of three macrophage types revealed that HdHMW and HdES significantly inhibited macrophage activation by LPS and poly(I:C), as measured by cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…For example, macrophages were implicated in the resolution of dextran-sodium sulfate-induced colitis in mice infected with Schistosoma mansoni (41). Given the possibility that helminthderived molecules might induce anti-inflammatory type macrophages (7,11), we tested the effect of an extract of H. diminuta and ES products on macrophage function. Analysis of three macrophage types revealed that HdHMW and HdES significantly inhibited macrophage activation by LPS and poly(I:C), as measured by cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, two groups of researchers have started to point out the relevance of glycoconjugates from T. crassiceps in immunomodulation. Thus, it has been demonstrated that glycans obtained from these metacestodes can modulate both innate [59] as well as acquired immune responses, and can even function as adjuvants favoring the Th2-type responses in vivo [49,50]. However, further studies are needed to define the main glycans involved in immune-modulation, as well as the target cells and the possible receptor for those molecules.…”
Section: Immunomodulation In Cysticercosismentioning
confidence: 95%
“…Specific inhibition of p38 MAPK results in substantial down-regulation of cytokine production in LPS-stimulated macrophages [47]. Thus, GC treatment during cysticercosis may influence the pro-inflammatory cytokine responses on granulomas, although a role for TLR-4 in response to Taenia antigens is still controversial [48][49][50].…”
Section: Vulnerable Target Molecules and Cells From The Immune Systemmentioning
confidence: 98%
“…Carbohydrates present in soluble antigens of this parasite are responsible for Th2 polarization in vivo [132] and induction of myeloid suppressor innate cells [133]. We have found that DC exposure to excreted/secreted products of high molecular weight from T. crassiceps metacestodes (TcES) induce an increment in MHCII expression but not in the costimulatory molecules CD80, CD86 or CD40 or in cytokine production.…”
Section: Helminth Parasitesmentioning
confidence: 99%